The Role of Entrepreneurship Learning Program for Encouraging the Students Entrepreneurial Motivation - Arif, Moh Erfan; Rosita, Nadiyah Hirfiyana; Pramono, Sigit (Faculty of Economics, State Islamic University of Maulana Malik Ibrahim Malang, 2020)
This study aims to determine the differences in entrepreneurial motivation in students who take part in the Management Entrepreneur Day (MED) program, including both implicit and explicit motivation in Management Department, Faculty of Economics and Business, Brawijaya University. This type of research is quantitative research with a method of collecting data in the form of probability sampling. The collected data was analyzed by applying SPSS analysis with a different test based on Analysis of Variance (ANOVA). The results of this study indicate that implicit motivation including motives for achievement (need for achievement) and motives for affiliation (need for affiliation) provides no difference in motivation (for entrepreneurship) in students who take MED. However, implicit motivation for controlling (need for power) presents a significant difference in the personal value among the students before (pre) and after (post) participating the MED activities. Whereas, explicit motivation including motives for achievement, depics a significant difference in students who take the MED program. Explicit motivation for affiliation (need for affiliation) and explicit motivation for controlling (need for power) indicates no difference in both before (pre) and after (post) participating in MED. From these results, the researchers concluded that the entrepreneurship program did not provide a significant change in entrepreneurial motivation among the participating students.